ANALISIS KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KARTU FLEXI DI BANDAR LAMPUNG - Andri Mitrawan; Venty Agustina (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2014)
This study aims to determine the magnitude of product quality influence on the Flexi Cardpurchase decision at PT Telkom Bandar Lampung. The method used in this study is a surveymethod. This research is descriptive and verificative. The population of this research was flexi cardconsumers who live in Enggal, Bandar Lampung as many as 3646 people.The total sample is 97respondents.Regression equation Y = 6.792 + 0.653 X. Hypothesis test results indicate that the variablequality of the product (X) significantly influence the purchase decision variable (Y) Flexi cards atPT Telkom Bandar Lampung, because the value of t count 7.463 > t table 1.660.